Social capital and sexual behavior among Ugandan university students - Agardh, Anette; Emmelin, Maria; Muriisa, Robert; Ostergren, Per-Olof (Global Health Action, 2010)
Background: Uganda has reduced its prevalence of HIV/AIDS from 18 to 6.5% within a decade. An important factor behind this might have been the response from faith-based voluntary organizations, which developed social capital for achieving this. Three behaviors have been targeted: Abstinence, Being faithful, and Condom use (the ABC strategy). The aim of this study was to explore the association between social capital and the ABC behaviors, especially with reference to religious factors. Methods: In 2005, 980 Ugandan university students responded to a self-administered questionnaire (response rate 80%). It assessed sociodemographic factors, social capital, importance of religion, sexual debut, number of lifetime sexual partners, and condom use. Logistic regression analysis was applied as the main analytical tool. Results: Thirty-seven percent of the male and 49% of the female students had not had sexual intercourse. Of those with sexual experience, 46% of the males and 23% of the females had had three or more lifetime sexual partners, and 32% of those males and 38% of the females stated they did not always use condoms with a new partner. Low trust in others was associated with a higher risk for not always using condoms with a new partner among male students (OR 1.7, 95% CI 1.1_2.8), and with a lower risk for sexual debut among female students (OR 0.5, 95% CI 0.3_0.9). Non-dominant bridging trust among male students was associated with a higher risk for having had many sexual partners (OR1.8, 95% CI 1.2_2.9). However, low trust in others was associated with a greater likelihood of sexual debut in men, while the opposite was true in women, and a similar pattern was also seen regarding a high number of lifetime sexual partners in individuals who were raised in families where religion played a major role. Conclusions: In general, social capital was associated with less risky sexual behavior in our sample. However, gender and role of religion modified the effect so that we cannot assume that risky sexual behavior is automatically reduced by increasing social capital in a highly religious society. The findings indicate the importance of understanding the interplay between social capital, religious influence, and gender issues in HIV/AIDS preventive strategies in Uganda.
Keywords: Youth; Sexual behavior; Sexual health; HIV/AIDS; Gender; Social capital; Religion; Uganda